Enhancement of engineered cardiac tissues by promotion of hiPSC-cardiomyocyte proliferation. (14th October 2021) - Hesselbarth, R; Esser, T U; Roshanbinfar, K; Struefer, S; Schubert, D W; Engel, F B
Abstract: Background/Introduction: Cardiac tissue engineering is a promising strategy to generate human cardiac tissues for modelling cardiac diseases, screening for therapeutic drugs, and repairing the injured heart. Yet, several issues remain to be resolved including the generation of tissues with high cardiomyocyte density. Purpose: Determining the effects of the induction of human-induced pluripotent stem cell-derived (hiPSC) cardiomyocyte proliferation post-fabrication. Methods: hiPSCs were differentiated into cardiomyocytes, embedded with or without CHIR990121 at three concentrations in a collagen pre-gel, and cast. The engineered cardiac tissues were then cultured in the absence or presence of CHIR99021 for up to 35 days. Hydrogels and engineered cardiac tissues were analysed utilizing rheology and assays to determine viability, proliferation, calcium flow, and contractility. Results: Here, we show that the integration of CHIR99021 in collagen I hydrogels promotes proliferation of hiPSC-cardiomyocytes post-fabrication improving contractility of and calcium flow in engineered cardiac tissues. Presence of CHIR99021 has no effect on the gelation kinetic or the mechanical properties of collagen I hydrogels. Analysis of cell density and proliferation based on Ki-67 staining indicates that integration of CHIR99021 together with external CHIR99021 stimulation increases hiPSC-cardiomyocyte number by ∼2-fold within 7 days post-fabrication. Analysis of the contractility of engineered cardiac tissues after another 3 days in the absence of external CHIR99021 shows that CHIR99021-induced hiPSC-cardiomyocyte proliferation results in synchronized calcium flow, rhythmic beating, increases speed of contraction and contraction amplitude, and reduces peak-to-peak time. The CHIR99021-stimulated engineered cardiac tissues exhibited spontaneous rhythmic contractions for at least 35 days. Conclusion: Collectively, our data demonstrate the potential of induced cardiomyocyte proliferation to enhance engineered cardiac tissues by increasing cardiomyocyte density and reducing arrhythmia. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft